A guide to the library of congress classification - Chan, Lois Mai (Libraries Unlimited, 1999)
The latest edition of this classic work #221;formerly Immroth's Guide to the Library of Congress Classification (Libraries Unlimited, 1990) #168; provides you with a basic understanding of the ever-evolving Library of Congress Classification system and its applications. After introducing the classification and giving a brief history of its development, the author presents readers with the general principles, structure, and format of the scheme.